Progression of Prothrombin Induced by Vitamin K Absence-II in Hepatocellular Carcinoma - Yang, Yang; Li, Guangbing; Lu, Ziwen; Liu, Yong; Kong, Junjie; Liu, Jun (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is the fifth most common cancer and the third leading cause of cancer-related death worldwide. Due to the lack of efficient tools for early detection, asymptomatic HCC patients are diagnosed at an advanced stage, leading to a poor prognosis. To improve survival, serum biomarker prothrombin induced by vitamin K absence-II (PIVKA-II) was under investigation. PIVKA-II is an abnormal protein produced in HCC. The coagulation function was insufficient due to the lack of Gla residues. Elevated PIVKA-II was associated with bad tumor behavior in terms of proliferation, metastasis, and invasion. Three major signaling pathways were proposed to clarify the mechanism. With the advantages including affordable, minimally invasive, convenient, and efficient, PIVKA-II could improve HCC management consisting of four aspects. First, PIVKA-II was an effective, and dynamic tool for improving HCC surveillance in high-risk populations. Changes in serum levels of PIVKA-II provided valuable molecular alterations information before imaging discovery. Second, PIVKA-II offered a complementary approach for HCC early detection. Compared to traditional diagnostic approaches, the combination of PIVKA-II and other biomarkers had better performance. Third, PIVKA-II was an indicator for the assessment of response to treatment in HCC. Preoperative assessment was for selecting personalized therapy and postoperative measurement was for assessing treatment efficacy. Fourth, PIVKA-II was considered as a prognostic predictor for HCC. Patients with elevated PIVKA-II were more likely to develop microvascular invasion, metastasis, and recurrence.